Pengaruh Literasi Keuangan, Religiusitas Dan Keamanan Terhadap Keputusan Menabung Di Bank Syariah (Studi Kasus Pada Generasi Milenial Di Kabupaten Sumenep) - Bayu Agus Subaidi; Liyanto Liyanto (Universitas Maritim AMNI Semarang, 2024)
Knowledge of finance, understanding of religiosity and security are three aspects that can influence a person's decision to make savings. By understanding these three aspects, it is hoped that the millennial generation will become a generation of quality for the progress of the nation and state. This research is a descriptivequantitative research using primary data. The sample used in this study was 95 millennial generation respondents. Data were obtained by distributing questionnaires both in person and online to respondents who met the qualifications as millennials or those born in 1990 to 2000. The data that was obtained was then processed with statistical software tools, namely SPSS version 26. The results in this study based on the regression test are: first, partially, the financial literacy variable has no influence on saving decisions. Second, partially, religiosity does not have a significant influence on the decision to save in Islamic banks. Third, partially, security has a significant influence on the decision to save in Islamic banks. And fourth, simultaneously, financial literacy, religiosity and security variables significantly influence the decision to save in Islamic banks.